Bullying no ambiente escolar - A perspectiva dos alunos da 3ª série do ensino médio de uma escola pública em Porto Nacional-TO - Silva, Maria Rufina Pereira da (Universidade Federal do Tocantins, 2021)
The aim of this study was to analyze bullying in the school environment from the perspective of students in the 3rd grade of high school in a public school in Porto Nacional - TO. The specific objectives were: to know the students' opinion about what it is and what are the practices of bullying in the school environment; identify if the researched school has a program to prevent and combat bullying in the school environment and indicate ways to combat bullying at school, in the classroom. The methodology of this research is characterized as exploratory descriptive of a qualitative and quantitative nature, based on bibliographic research and field observations in digital way, using Google Forms with the students of the 3rd grade of High School of a Public School in Porto Nacional - TO . In times of pandemic of the New Corona Virus (COVID - 19) the questionnaires were sent to the students of the Public School under study by a digital tool (Google Forms). The results show that bullying in the school environment is a problem and that there is an interconnection between the school, the teacher, including the geography teacher, the family and society in prevention, combat and intervention.